2020
DOI: 10.1111/ssqu.12907
|View full text |Cite
|
Sign up to set email alerts
|

Terrorist Attacks, Stereotyping, and Attitudes Toward Immigrants: The Case of the Manchester Bombing

Abstract: Objective. Growing research focusing on citizens' psychological reactions to terrorism finds that attacks perpetrated by individuals belonging to Muslim minorities increase negative attitudes toward immigrants as a whole. We argue that this empirical regularity might be explained by stereotyping, which produces immediate emotional reactions among people holding exogenously positive/neutral attitudes toward immigrants. Methods. We employ a quasi-experimental before-after design based on the Manchester bombing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 46 publications
0
9
0
1
Order By: Relevance
“…Recent ISIS terrorist attacks in Europe have intensified fear sentiments among native populations and immigrants (Mancosu and Ferrín Pereira 2021). Several scholars concluded that the dynamics of intolerance and the perception of immigrants as a threat were the results of the created tensions after the 9/11 attacks, the 2004 bombings in Madrid, London 2005, Charlie Hebdo 2015, and Paris 2018(Miguel-Tobal et al 2006Bar-Tal et al, 2012;Huddy et al 2005;Skitka et al 2004;Ben-Ezra et al 2015;Vasilopoulos et al 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Recent ISIS terrorist attacks in Europe have intensified fear sentiments among native populations and immigrants (Mancosu and Ferrín Pereira 2021). Several scholars concluded that the dynamics of intolerance and the perception of immigrants as a threat were the results of the created tensions after the 9/11 attacks, the 2004 bombings in Madrid, London 2005, Charlie Hebdo 2015, and Paris 2018(Miguel-Tobal et al 2006Bar-Tal et al, 2012;Huddy et al 2005;Skitka et al 2004;Ben-Ezra et al 2015;Vasilopoulos et al 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…2019). They draw on an antagonistic relationship between the in‐group and out‐groups and portray immigrants as violating their perceived “national norm,” that is, a monocultural society with limited space for immigrants who would alter the country's culture, economy, and sociodemographic make‐up (Golder 2016; Lucassen and Lubbers 2012; Mancosu and Pereira 2021). Far‐right parties seek to preserve the underlying values, unity, and identity of the nation‐state by offering “nationalist” solutions to societal problems (Vasilopoulou and Halikiopoulou 2015).…”
Section: Hypotheses On Far‐right Votingmentioning
confidence: 99%
“…Because this is less true for the Chechnya attack in 2008, we ran our analysis with and without this case. 4 The lower panel in Figure 1 shows the results of an imbalance analysis (Ferrín et al, 2020;Legewie, 2013;Mancosu & Ferrín Pereira, 2021;Rubin, 2001), which assesses whether the respondents in the pre-and post-intervention groups are sufficiently comparable regarding our included exogenous covariates. The x-axis provides the standardized difference in means and the y-axis provides the variance ratio of the covariates age, education years, gender and household net income.…”
Section: A Priori Assumption Checksmentioning
confidence: 99%
“…Previous research has examined how terrorist attacks influence a variety of societal outcomes, including public trust in government institutions (Dinesen & Jaeger, 2013;Fenn & Brunton-Smith, 2021;Godefroidt, 2022;Perrin & Smolek, 2009), immigration attitudes (Breton & Eady, 2021;Czymara et al, 2022;Jungkunz et al, 2019;Larsen et al, 2020;Legewie, 2013;Mancosu & Ferrín Pereira, 2021;Nägel & Lutter, 2020), well-being (Coupe, 2017;Metcalfe et al, 2011;Tsai & Venkataramani, 2015), and political behavior (Balcells & Torrats-Espinosa, 2018;Finseraas et al, 2011;Montalvo, 2011). One of the more consistent findings is the collective increase in support for political institutions following attacks (Godefroidt, 2022;Van Hauwaert & Huber, 2020).…”
Section: Introductionmentioning
confidence: 99%